THE ANALYSIS OF MONITORING SYSTEMS TO MANAGE EMERGENCY POPULATION WARNING - Vladimir Viktorovich Naumenko; Sergei Aleksandrovich Fedorov; Aleksandr Sergeevich Moskalenko; Ruslan Ibragimovich Kasimov (Современная наука и инновации)
He article analyzes the features and technological decisions used in modern laboratory monitoring systems applied in complex systems of emergency population warning